Active learning for image preparation of automatic vending machine (AVM) employing transfer learning method. (November 2020) - Li, Fang; Zeng, Min; Xiao, Jia; Li, Xiaojun; Li, Yuanyuan; Hu, Guosheng
Abstract: In this paper, we employed active learning methods to prepare annotated images for our training of automatic vending machine (AVM) system, in order to minimize human annotation cost. Due to the tiny data of our system, transfer learning approach is used by implementing the already trained Yolov3-tiny model for COCO dataset as our training start. Also, we evaluated the effectiveness of 3 annotation strategies: smallest annotation area (SAA), largest annotation area (LAA) and moderate annotation area (MAA), for photos of top views from above. The results show that the idea of employing active learning methods to prepare annotated data is feasible. Also, the annotation strategy of MAA demonstrates the superior performance, for its enough object area and the least background area.